Plasma Levels of Long-Acting Injectable Antipsychotics in Outpatient Care: A Retrospective Analysis - Hýža M (Dove Medical Press, 2021)
Martin Hýža,1,2 Petr Šilhán,1,2 Eva Češková,1,2 Tomáš Skřont,1 Ivana Kacířová,3,4 Romana Uřinovská,3 Milan Grundmann4 1Department of Psychiatry, University Hospital Ostrava, Ostrava, Czech Republic; 2Department of Clinical Neurosciences, Faculty of Medicine, University of Ostrava, Ostrava, Czech Republic; 3Department of Clinical Pharmacology, Institute of Laboratory Diagnostics, University Hospital Ostrava, Ostrava, Czech Republic; 4Department of Clinical Pharmacology, Faculty of Medicine, University of Ostrava, Ostrava, Czech RepublicCorrespondence: Petr ŠilhánDepartment of Psychiatry, University Hospital Ostrava, 17. Listopadu 1790, Ostrava, 708 52, Czech RepublicTel +420 59 737 3145Fax +420 59 737 3314Email petr.silhan@fno.czPurpose: Antipsychotic efficacy in schizophrenia depends on its availability in the body. Although therapeutic outcomes remain still far from satisfactory, therapeutic drug monitoring is not a common part of clinical practice during treatment with long-acting injectable antipsychotics (LAI AP). The real effectiveness of LAI AP is thus uncertain.Patients and Methods: We made a retrospective evaluation of plasma levels of LAI AP. Collection of blood samples was performed just before the drug application and one week later. Forty patients with a stabilized clinical condition and steady-state plasma levels were included.Results: In the observed cohort of patients, flupentixol decanoate (n = 23) was the most often used drug, followed by fluphenazine decanoate (n = 7), haloperidol decanoate (n = 5), paliperidone palmitate (n = 3), and risperidone microspheres (n = 2). Just 5 of 40 patients were treated with a monotherapy. In the period before the application, 60% of the patients did not reach the therapeutic reference range (TRR) and 20% of the patients had an undetectable plasma level. At the time of collection of the second blood samples performed after 7 days, 24% of the patients were under the TRR.Conclusion: We have found a surprisingly high incidence of plasma levels under the TRR in patients treated with LAI AP. Notwithstanding individual variability in pharmacokinetics, it seems that LAI AP may be underdosed in usual clinical practice.Keywords: therapeutic drug monitoring, antipsychotics, psychotic disorders, schizophrenia